AGRICULTURAL ACTIVITIES LAND COVER CHANGE EFFECT IN KAZ (IDA) MOUNTAINS NATIONAL PARK (1975-2005) - Mehmet ÖZCANLI (Fırat University, 2019)
Of Kaz Mountain masses situated on Biga peninsula in South Marmara Part of Marmara Region, the areas extending from Zeytinli Stream to Mihli Stream in Balikesir Province and up to the mountain summit covering a total area of 21.300 ha in southern part were given the status of national park in 1993, especially due to rich flora and fauna in this area. The purpose of this study is to determine land cover types in Kaz Mountains National Park and to investigate the effects of land cover forming as a result of agricultural activities on natural land cover of the area. The hypothesis of the study is that “Agricultural activities have an important role in changing and deteriorating natural land cover in Kaz Mountains National Park”. The study method includes the use of CIS techniques in mapping and analyzing time and spatial variables of land cover. Landsat TM satellite images (1975-1980-1984-2000-2005) were obtained and then, correlation analysis between the characteristics of natural land cover and agricultural areas and controlled classification method were performed. The raw data of the controlled classification were used for land classifications including large leafed forest, coniferous forest, bare rocks, forest clearance, agricultural land and unknown area and these areas were analyzed. The methodological importance of the study is to emphasize the importance of Geographic Information Systems (CIS) and remote sensing in determining the characteristics of land use. The analysis results indicate the presence of spatial and proportional changes in natural land cover and agricultural land use in Kaz Mountain National Park between 1975 and 2005